Estrategias para fomentar el hábito de lectura en los estudiantes de Educación General Básica - Analuiza Toapanta, Jessica Maribel (2022)
The present degree work focused on the problem evidenced in the "Coronel Germánico Rivadeneira Valencia" School, where it has been observed that the students present a low level of development of the reading habit, since the students show reactions of rejection and demotivation towards reading, they are not interested in looking for complementary reading material for their formative process or for recreation and during their free time they do not carry out reading activities. The objective of the research was to encourage the habit of reading by means of didactic strategies centered on the process in students in the ninth year of General Basic Education at the "Coronel Germánico Rivadeneira Valencia" School. The methodology applied had a quantitative paradigm, with a positivist approach, the level of research was descriptive, the research design was quasi-experimental and longitudinal, through the application of the deductive method. The techniques used were observation, interview and survey, through the application of an observation form to the students, the structured questionnaire of open questions to the authority of the institution and the survey questionnaires to teachers and parents. The diagnosis carried out with the students of the ninth year of EGB allowed corroborating the low level of development of the reading habit. Therefore, a proposal was developed using didactic strategies focused on the process, didactic games and strategies mediated by technological tools. This resulted in a significant improvement in the development of the reading habit, in relation to the categories of efficient reading, reading comprehension, motivation, autonomy and enjoyment of reading, where there has been a positive improvement of between 25 and 45 percentage points between the pre-test and the post-test.